Holy Disobedience: Political Resistance in the London Catholic Worker Community. (4th December 2018) - Blackman, Anna
Abstract : This article focuses on the way in which the Catholic Worker Movement has incorporated ecclesial practices into their political resistance work in ways that redefine the conventional boundaries of both the "religious" and the "political." Historically the movement emerged from the Catholic social teaching tradition, and draws on Catholic religious ritual in its protest. However, it reinterprets the tradition through a Christian anarchist lens leading to a much more radical understanding of the Church's political role. Drawing on an ethnographic study of the London Catholic Worker community this essay explores how the movement's commitment to resistance work stems from deep theological and spiritual motivations, analysing how it uses these to form a distinct set of religious-political practices.